Evaluation of Genetic Diversity and Heritability on Soybeans Agronomic Characters in M4 by Gamma Irradiation - Sari, Yunita Mahda; Kusmiyati, Florentina; Anwar, Syaiful (Journal of Tropical Crop Science and Technology, 2021)
The production of soybeans can be increase by breeding for tolerance soybeans at saline soil. Mutation by gamma rays is one of a breeding technique that can be modifiy plant's genetic. The soybeans that used was induced by gamma rays with dosis 160 Gy, 208 Gy, 256 Gy, 352 Gy, and 400 Gy. The research objective was to evaluate the genetic variability and heritability for some characters of M4 soybean mutations resulting from gamma irradiation mutations.The material used consisted of 18 genotypes of M4. This research was conducted at Agrotechopark, Faculty of Animal and Agricultural Science, Diponegoro University from July to November 2019. The experimental was arranged in a completely randomized design (CDR) monofactor with 18 genotypes of black soybeans and Detam-3 Prida as controls. The results showed that genetic diversity observed in the overall character of plants except flowering age, number of empty pods, weight of one seed, and weight of 100 grains. The result of heritability showed a high heritability on the parameters of plant height, age of harvest, total number of seeds, number of filled pods, total number of pods, total pod weight, and total seed weight. The value of moderate heritability is found on the parameters of the number of leaves, and then the low heritability is on the parameters of flowering age, number of empty pods, weight of 1 seed, and weight of 100 grains.